A flexible enantioselective approach to 2, 5-disubstituted cis-decahydroquinolines. (10th September 2022) - Lang, Qi-Wei; Qian, Xiang-Yang; He, Xiu-Lin; Geng, Hui; Zheng, Jian-Feng; Huang, Pei-Qiang
Abstract: A flexible asymmetric approach to 2, 5-disubstituted cis -decahydroquinolines (DHQs) ring system from glutaraldehyde and methyl ( E )-5-nitropent-4-enoate is reported. The enantioselective organocatalytic domino Michael/Henry reaction, subsequent one-pot, four-step transformation involving desulfurization, concomitant nitro and alkene reduction and cyclization, and the one-pot amide reductive alkylation method are the key steps responsible for the stereoselective syntheses of 2, 5 - di -epi-cis -195 A, N -Bn-5- epi-cis -275 B' and N -Bn- cis -249D. Graphical abstract: Image 1